The Effect of Finger Painting towards Fine Motor Skill of Intellectual Disability - Anisa Kurniawati; Wiwik Dwi Hastuti; Henry Praherdhiono (Department of Special Education, 2018)
Fine motor skills have important role for the children’s life, so it must be stimulating and developing maximally. One of them is finger painting. Finger painting is paint directly using finger without help of tools or brush by scratching coloring pulp made from safe material for children on blank paper according to the childrens‘ creativity. This research intends to explain the condition of students with intellectual disability before giving treatments, the condition of students with intellectual disability after giving treatments and the effect of finger painting towards fine motor skill students with intellectual disability. This research used quantitative research methods with quasi experimental technique time series design. The subject of this research was 6 students. This data was taken from the result of pretest dan posttest that each phase was done four times, this is purpose to measure the stability of student’s condition. In the test phase of analysis, this research was using Wilcoxon Test. The results of this observation before giving finger painting, the students’ fine motor skill was still low. Their finger was seen rigid and their finger coordination was not good proven that pretest score average was 45,2 including fewer categories and after giving finger painting, the students’ fine motor skill was increasing with evidence of posttest score average was 80,6 and it includes to excellent categories. Base on the data analysis, it can be concluded that there was a significant effect on students with intellectual disability before and after giving treatments with finger painting on learning process. Finger painting is very affected towards fine motor skill of students with intellectual disability at 5th grade of SDLB Kemala Bhayangkari Trenggalek.